Undiagnosed interrupted aortic arch in a 59-year-old male patient with severe aortic valve stenosis: A case report and literature review - Mehrpooya, Maryam (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2014)
BACKGROUND: Interrupted aortic arch (IAA) is defined by a lack of the luminal continuity between the ascending and descending thoracic aorta. It is a rare, severe congenital heart defect which without surgery is associated with high mortality in the neonatal period. The aims of this study were to present a case with IAA who was alive until the age of 59 years without any surgical intervention and to review the literatures that have presented IAA cases. CASE REPORT: The patient was admitted with respiratory distress and pulmonary edema. Echocardiography showed the sever stenosis in aortic valve and sever left ventricular dysfunction. Cardiac catheterization and angiography confirmed interrupted aorta (type A). The descending thoracic aorta was supplied by extensive collateral vessels from the vertebrobasilar system down to the posterior chest wall and the spine. Surgical correction including coronary artery bypass graft and aortic valve replacement and repair of interruption of the aorta was performed. Three weeks later the patient was died due to uncontrollable gastrointestinal bleeding and hospital acquired pneumonia. We described diagnosis and management of our case. CONCLUSION: This case was very interesting for us, because the patient had not been diagnosed until the recent presentation. Similar cases with this diagnosis do not reach adulthood, but our patient was alive up to 59 years of age.